Development of a Topical Cream from the Ethanolic of Agave sisalana Residues with Anti-Inflammatory and Analgesic Properties - Fracasso, Júlia Amanda Rodrigues [UNESP]; Takahashi, Myriam Emiko [UNESP]; da Costa, Luísa Taynara Silvério [UNESP]; Barbosa, Debora Barros [UNESP]; Soares, Bruno Araújo [UNESP]; Pereira Martins, Wellington Ricardo [UNESP]; Zoppe, Natália Alves [UNESP]; Marques, Joana; Marques, Maria P. M.; da Silva, Aida Moreira; Barroca, Maria João; Ximenes, Valdecir Farias; et al. (MDPI, 2024)
Brazil is the largest producer in the world of the species Agave sisalana, sisal. The residue of the sisal, which is the result of the extraction of fibers from its leaves, represents 95% of its weight. Considering that sisal leaves have high concentrations of sapogenins and aiming at a future phytotherapeutic, in this study, the alcoholic fraction of sisal, AFS, was developed, and the sapogenins were characterized. In vitro, the cytotoxicity (MTT) and the anti-inflammatory effect of AFS (phagocytosis and hemolysis inhibition) were evaluated. In vivo, the analgesic (formalin test—FT) and anti-inflammatory (paw edema test—PET) activities of AFS, orally, and the cream containing AFS, topical, were analyzed. The results demonstrated that AFS contains hecogenin and tigogenin and is not cytotoxic. In vitro, 0.5, 1, and 2 mg/mL of AFS showed anti-inflammatory activity similar to the positive control (PC). In the FT, the dose of 25 mg/kg did not differ from the PC in the neurogenic phase (p > 0.05). In the PET, 25 and 50 mg/kg of AFS differed from the negative control (NC) (p < 0.05), and the cream with AFS (5 mg/g) showed activity similar to the PC. The therapeutic activities of AFS probably result from sapogenins. In the future, we expect to develop an anti-inflammatory from the thousands of tons of sisal waste discarded in Brazil.
Keywords: bioeconomy; phytotherapy; sisal; sustainability